Maximization of ICRF power by SOL density tailoring with local gas injection. (2nd March 2016) - Jacquet, P.; Goniche, M.; Bobkov, V.; Lerche, E.; Pinsker, R.I.; Pitts, R.A.; Zhang, W.; Colas, L.; Hosea, J.; Moriyama, S.; Wang, S.-J.; Wukitch, S.; et al.
Abstract: Experiments have been performed under the coordination of the International Tokamak Physics Activity (ITPA) on several tokamaks, including ASDEX Upgrade (AUG), JET and DIII-D, to characterize the increased Ion cyclotron range of frequency (ICRF) antenna loading achieved by optimizing the position of gas injection relative to the RF antennas. On DIII-D, AUG and JET (with the ITER-Like Wall) a 50% increase in the antenna loading was observed when injecting deuterium in ELMy H-mode plasmas using mid-plane inlets close to the powered antennas instead of divertor injection and, with smaller improvement when using gas inlets located at the top of the machine. The gas injection rate required for such improvements (~0.7  ×  10 22 el s −1 in AUG, ~1.0  ×  10 22 el s −1 in JET) is compatible with the use of this technique to optimize ICRF heating during the development of plasma scenarios and no degradation of confinement was observed when using the mid-plane or top inlets compared with divertor valves. An increase in the scrape-off layer (SOL) density was measured when switching gas injection from divertor to outer mid-plane or top. On JET and DIII-D, the measured SOL density increase when using main chamber puffing is consistent with the antenna coupling resistance increase provided that the distance between the measurement lines of sight and the injection location is taken into account. Optimized gas injection was also found to be beneficial for reducing tungsten (W) sputtering at the AUG antenna limiters, and also to reduce slightly the W and nickel (Ni) content in JET plasmas. Modeling the specific effects of divertor/top/mid-plane injection on the outer mid-plane density was carried out using both the EDGE2D-EIRENE and EMC3-EIRENE plasma boundary code packages; simulations indeed indicate that outer mid-plane gas injection maximizes the density in the mid-plane close to the injection point with qualitative agreement with the AUG SOL density measurements for EMC3-EIRENE. Field line tracing for ITER in the 15 MA Q DT   =  10 reference scenario indicates that the planned gas injection system could be used to tailor the density in front the antennas. Benchmarking of EMC3-EIRENE against AUG and JET data is planned as a first step towards the ITER SOL modelling required to quantify the effect of gas injection on the SOL density in front of the antennas.